The Historical Basis of Aceh Development - Özay, Mehmet (Journal of History Culture and Art Research, 2012)
The Historical Basis of Aceh Socio-Economics Development (1511-1904) Abstract It is vital to see the connection between experiences in history and contemporary developments in almost all corners of the world. Regions which appear as leading powers in economic developments have historically had their own particular dynamics. In the event that the dynamics of the past uncover the true means to go forward, it will trigger the path of progress at an unexpected time, when similar conditions are met. Taking this condition into account with regard to Aceh, we see that Aceh has been a potential candidate for the newly emerging economic development centers in Southeast Asia after the disastrous event on 26th December, 2004, pursuant to which the Memorandum of Understanding (MoU) in Helsinki was signed by the related sides on 15th August, 2005. To assess and evaluate the possibilities and opportunities that open up before Aceh Province by virtue of the MoU, the tradition of economic developments in history should be revisited and evaluated. It might be assumed that the reflections from the past will certainly enlighten the future. This article suggests that the economic development of the Sultanate of Aceh Darussalam in the past might be a starting point for all parties in Aceh Province to deduce exactly how to deal with prevailing difficulties so as to commence economic progress in the region. It is considered that historical experiences are repetitive. The significance of Aceh was based on several diverse factors, primarily its state structure, economic activities, and geo-strategic position on the extreme northwest of Sumatra, that allowed it to be a part of the international sea trade between the east and the west between the 16th and 19th centuries. These characteristics propelled Aceh to become not only a prominent region, but also gain supremacy in global partnerships in the business of international trade. After the peace agreement celebrations, it is the need of the hour for all social and economic sectors in Aceh Province to trigger the potentiality of their region by looking at their flourishing past. Les Fondements Historiques Du Développement Socio-Economique d’Aceh (1511-1904) Résumé Il existe une relation remarquable entre le développement économique actuel des pays et des régions et leurs expériences vécues dans le passé. Dans ce contexte, on peut suggérer que cette relation pourrait être basée sur les dynamiques propres à ces pays. En effet, avec la découverte de ces dynamiques qui existait dans le passé, on peut prévoir que certaines régions d’aujourd’hui peuvent de nouveau occuper une place sur la scène mondiale si des conditions similaires existent encore. Dans cet article, nous étudions que l’Aceh – si elle s'accorde aux développements récents dans le monde– a une potentialité qui lui donne une place méritée surtout dans les stratégies de développement socio-économique de l’Asie du Sud-ouest. Pour comprendre à quoi ce potentiel correspond, il faudra analyser la structure de l’économie et les interactions économiques émergeant de l’existence politique de l’Ache plus particulièrement à partir du début de 16ème jusqu’au début du 20èmesiècle. Nous pensons que, au cours des siècles, la tradition étatique du Sultanat d’Aceh – qui lui a permis d’être l’objet des relations commerciales internationales entre l’est et l'ouest – ses activités économiques et sa position géostratégique seront des références pour son avenir. Açe’deki Sosyo-Ekonomik Kalkınmanın Tarihsel Temelleri (1511-1904) Özet Ülkelerin ve coğrafyaların bugünkü ekonomik gelişmişlikleri ile geçmişte yaşadıkları tecrübeler arasında dikkate değer bir ilişki vardır. Bu bağlamda, bu ilişkinin söz konusu bölgelerin kendine has dinamiklere dayandığı ileri sürülebilir. Öyle ki, geçmişte var olan bu dinamiklerin keşfiyle, bugün kimi bölgelerin, benzer koşulların hasıl olması halinde, yeniden dünya sahnesinde varlık bulabileceklerini öngörebiliriz. Bu makalede, Açe’nin, son dönemde yaşanan gelişmeler ışığında ele alındığında, dünyanın özellikle de Güneydoğu Asya’nın sosyo-ekonomik kalkınma stratejileri içerisinde hak ettiği yeri alabilecek bir potansiyele sahip olduğu üzerinde durulmaktadır. Bu potansiyelin nelere tekabül ettiği, Açe’nin özellikle 16. yüzyıl başlarından 20. yüzyıl başlarına kadar devam eden siyasi varlığı içerisinde ortaya çıkan ekonomik yapısı ve ekonomik etkileşimlerinin analiz edilmesiyle yakından ilintilidir. Açe İslam Sultanlığı’nı sözü edilen yüzyıllar içerisinde, Doğu-Batı arasındaki uluslararası ticaret ilişkilerine konu olmasını sağlayan devlet geleneği, ekonomik aktiviteleri ve jeo-stratejik konumunun Açe’nin geleceği için bir referans olacağını düşünüyoruz. الأساس التاريخي للتنمية الاجتماعية والاقتصادية في اتشيه (1511-1904)a ملخص لا شك أن هناك علاقة وثيقة بين تجارب الدول والمناطق المختلفة في الماضي وبين الحالة الإقتصادية التي تعيشها تلك الدول والمناطق اليوم. هذه العلاقة التي كانت موجودة في الماضي والتي نشأت على أساس عوامل وظروف خاصة بتلك الدول والمناطق، يمكن اكتشافها مرة أخرى اليوم وتطويرها على الساحة العالمية في بعض المناطق الأخرى من العالم لظروف مشابهة. وهذا البحث محاولة لتحليل واقع مدينة اتشيه، وبيان الاستراتيجيات المطلوبة لها في ضوء التغيرات السياسية والاقتصادية التي يمر بها العالم وخاصة جنوب شرق آسيا في الآونة الأخيرة من جانب. ومن جانب آخر محاولة اكتشاف مدى وجود العلاقة بين ما كانت تملك من إمكانات واستراتيجيات سياسية واقتصادية هائلة في الماضي، خاصة في القرن السادس عشر وبداية القرن العشرين الميلادي، وحالتها السياسية والإقتصادية اليوم. وأخيرا نعتقد أن سلطنة اتشيه بما لها من تاريخ عريق وموقع جغرافي استراتيجي خاصة في مجال التجارة الدولية والربط بين الشرق والغرب مؤهلة لمستقبل أفضل.